Association Between Dietary Patterns and Chronic Disease Among Female Students, prince Sattam University, Al-Kharj, Saudi Arabia - Al-Dayan, Noura (Progress in Nutrition, 2022)
Dietary patterns reflects food and nutrient consumption and may be indicator to predict disease risk .An occurrence of nutrients in the required quantities is necessary from the daily diet to maintain the healthy food consumption pattern and play a vital role in health balance determinants. The aim of this study is to investigate the behavior of dietary pattern, nutritional status associated with physical activity and related health diseases in university population. This cross-sectional study involved 368 female undergraduate university students, involved in the study. The data, gathered a pretested, organized self-administered questionnaires organized self-administered questionnaires related to sociodemographic, anthropometric, eating attitudes, physical activity and health related issues were analyzed. The Study results showed that mean age 22.5 ± 2.4 years of student’s response to the survey. More than half of the respondents 201 (54.4%) skipped breakfast. Majority of the students 324 (88.0%) ate snacks and juice every day. Over two-third of the students 263 (71.4%) had normal BMI, whereas 56 (15.2%) were underweight, and 49 (13.4%) were overweight. Over half of the respondents 203 (55.1%) had high dietary diversity whereas, 67 (18.2%) had moderate diet and 98 (26.6%) had low dietary diversity. One fourth of the respondents 87 (23.6%) performed physical activity every day. Related to health issues most of the students 95 (28%) had anemia and 52 (14.8%) were facing problem with hormonal imbalance. In conclusion, Food consumption associated with BMI which related to physical activity and nutrition related disorders become a health issues in all societies of the world. Encourage the students to improve their eating behavior, practices physical activity by regular nutrition education program by the institution.